Mass measurements on neutron-deficient Sr and neutron-rich Sn isotopes with the ISOLTRAP mass spectrometer - Sikler, Günther; Herfurth, Frank; Kluge, Heinz-Jürgen (Nuclear physics. A, Nuclear and hadronic physics, 2005)
The atomic masses of 76,77,80,81,86,88Sr and 124,129,130,131,132Sn were measured by means of the Penning trap mass spectrometer ISOLTRAP at ISOLDE/CERN. 76Sr is now the heaviest N=Z nucleus for which the mass is measured to a precision better than 35 keV. For the tin isotopes in the close vicinity of the doubly magic nucleus 132Sn, mass uncertainties below 20 keV were achieved. An atomic mass evaluation was carried out taking other experimental mass values into account by performing a least-squares adjustment. Some discrepancies between older experimental values and the ones reported here emerged and were resolved. The results of the new adjustment and their impact will be presented.
Gesehen am 28.02.2020